2010
DOI: 10.1007/s12012-010-9098-3
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effects of Vanillic Acid on Lipids, Bax, Bcl-2 and Myocardial Infarct Size on Isoproterenol-Induced Myocardial Infarcted Rats: A Biochemical and In Vitro Study

Abstract: We made an attempt to evaluate the preventive effects of vanillic acid on isoproterenol-induced myocardial infarcted rats. Rats were pretreated with vanillic acid (5 and 10 mg/kg) daily for 10 days. After pretreatment, rats were injected with isoproterenol (100 mg/kg) at an interval of 24 h for 2 days to induce myocardial infarction. Isoproterenol induction increased the activity of serum creatine kinase-MB and increased the levels of serum and heart cholesterol, triglycerides, free fatty acids in rats. It inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 24 publications
3
31
0
1
Order By: Relevance
“…These also can scavenge free radical species and, therefore, exert an antioxidant effects as hydroxycinnamic acids do. Several studies have demonstrated the antioxidant capacities of 4-hydroxybenzoic acid and vanillic acid using 1,1-diphenyl-2-picrylhydrazyl (DPPH) (49,50). Although these two compounds, which were isolated from walnut kernels in their study, showed only relatively low scavenging activities, they are still potential antioxidant components (49).…”
Section: Hydroxybenzoic Acids From Lignin Hydrolysismentioning
confidence: 99%
See 3 more Smart Citations
“…These also can scavenge free radical species and, therefore, exert an antioxidant effects as hydroxycinnamic acids do. Several studies have demonstrated the antioxidant capacities of 4-hydroxybenzoic acid and vanillic acid using 1,1-diphenyl-2-picrylhydrazyl (DPPH) (49,50). Although these two compounds, which were isolated from walnut kernels in their study, showed only relatively low scavenging activities, they are still potential antioxidant components (49).…”
Section: Hydroxybenzoic Acids From Lignin Hydrolysismentioning
confidence: 99%
“…Although these two compounds, which were isolated from walnut kernels in their study, showed only relatively low scavenging activities, they are still potential antioxidant components (49). Moreover, it was shown that vanillic acid scavenges the stable radical species, DPPH, in a dose-dependent manner, with the highest scavenging effects seen with 60 μM of vanillic acid (50). Due to the antioxidant activity of vanillic acid, like the hydroxycinnamic acids above it has protective capabilities, such as hepatoprotective effects, against several diseases which are associated with oxidative deterioration (50)(51)(52).…”
Section: Hydroxybenzoic Acids From Lignin Hydrolysismentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, VA can scavenge free radical species, having cardioprotective properties, and it could repress fibrogenesis and inflammation in the chronically injured liver [35]- [37]. VN is used as a flavoring agent in food and cosmetics, having well-studied antimicrobial [38] [39], anti-mutagenic, antioxidant, and anti-carcinogenic activities [39]- [41].…”
Section: Resultsmentioning
confidence: 99%